Relationship between critical thinking dispositions, perceptions towards teachers, learning approaches and critical thinking skills among university Students - Wan Sulaiman, Wan Shahrazad; Abdul Rahman, Wan Rafaei; Dzulkifli, Mariam Adawiah (2007)
Preparing students to be able to think critically is a goal of many professionals in higher education and also a quality sought by employers of university graduates. Therefore, critical thinking skill is considered an important variable in the process of students’ learning. This study attempts to examine the predictive relationships of student characteristics, students’ perceptions towards teachers and learning approaches towards critical thinking skills. A questionnaire to measure critical thinking skills will be constructed. Apart from that, three other instruments will be used in gathering data, namely the Critical Thinking Dispositions Inventory (CTDI), the students’ perceptions of Teachers’ Approaches to Teaching and the Revised Study Process Questionnaire (R-SPQ-2F). Participants will comprise university students from International Islamic University Malaysia (IIUM), University Kebangsaan Malaysia (UKM), University Technology Mara (UiTM) and University of Malaya (UM). The data will be analyzed using statistical method such as alpha Cronbach, principal component analysis, Pearson correlation and structural equation modeling. Results of significant relationships among are variables are expected from the analysis.